Liber Uricrisiarum : a reading edition - Daniel, Henry (Medical writer) (University of Toronto Press, 2020)
"Henry Daniel's Liber Uricrisiarum is the earliest known work of academic medicine written in Middle English, presented here for the first time in a complete edition. Working in the late 1370s, Daniel combined authoritative medicine from written sources with his own personal experience, creating a text that stands out for its linguistic originality, intellectual scope, and wide circulation. Extant in over three dozen manuscript witnesses and two early modern print copies, Liber Uricrisiarum describes medieval humoral theory, anatomy, physiology, disease, medical astronomy, reproductive processes, and more, all within the broader context of uroscopic diagnosis."--